KAWIN BEDA AGAMA DAN NASAB ANAK (Studi analisis terhadap Kompilasi Hukum Islam) - Dr. Andi Herawati, M.Ag (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2017)
Marriage is the nature of man to meet the demands of human instincts are basic. Therefore, Islam establishes a legitimate way to meet those needs with the marriage contract (through the marriage road). Marriage in Islam aims to fortify people from promiscuity that can degrade and destroy human dignity. Islam considers the formation of the family through legitimate marriages based on the same creed as an effective means of sustaining the generation of destruction and protecting society from chaos, especially children born of the marriage. Thus the child will not be confused to establish a religion that he embraced and derivatives also clear and easy to know.